Influence of Subjective/Objective Status and Possible Pathways of Young Migrants’ Life Satisfaction and Psychological Distress in China - Chiang, Yi-Chen; Chu, Meijie; Zhao, Yuchen; Li, Xian; Li, An; Lee, Chun-Yang; Hsueh, Shao-Chieh; Zhang, Shuoxun (Frontiers in Psychology, 2021)
Young migrants have been the major migrant labor force in urban China. But they may be more vulnerable in quality of life and mental health than other groups, due to their personal characteristic and some social/community policies or management measures. It highlights the need to focus on psychological wellbeing and probe driving and reinforcing factors that influence their mental health. This study aimed to investigate the influence of subjective/objective status and possible pathways of young migrants' life satisfaction and psychological distress. Data on 9838 young migrants in the China Migrants Dynamic Survey were analyzed by LISREL 8.8. A total of 94.03% migrated for jobs or business. Subjective status, including subjective socioeconomic status, social adaptation, and psychological integration, had positive effects on life satisfaction, whereas social adaptation and psychological integration negatively affected psychological distress. Objective status, including objective socioeconomic status and health insurance, had adverse effects on life satisfaction, whereas they positively affected psychological distress. Social participation and city belonging had only significant positive mediating roles on life satisfaction. It is essential to increase social adaptation and decrease integration stress according to younger internal migrants’ practical needs. It is also necessary to enhance community/social resources and activities in the context of developing sustainability in the community to assist in mental health promotion.